SARS-CoV-2 Infection in Pregnancy – a Review of the Current Literature and Possible Impact on Maternal and Neonatal Outcome - Stumpfe, Florian M.; Titzmann, Adriana; Schneider, Michael O.; Stelzl, Patrick; Kehl, Sven; Fasching, Peter A.; Beckmann, Matthias W.; Ensser, Armin (Geburtshilfe und Frauenheilkunde, 2020)
In December 2019, cases of pneumonia of unknown cause first started to appear in Wuhan in China; subsequently, a new coronavirus was soon identified as the cause of the illness, now known as Coronavirus Disease 2019 (COVID-19). Since then, infections have been confirmed worldwide in numerous countries, with the number of cases steadily rising. The aim of the present review is to provide an overview of the new severe acute respiratory syndrome (SARS) coronavirus 2 (SARS-CoV-2) and, in particular, to deduce from it potential risks and complications for pregnant patients. For this purpose, the available literature on cases of infection in pregnancy during the SARS epidemic of 2002/2003, the MERS (Middle East respiratory syndrome) epidemic ongoing since 2012, as well as recent publications on cases infected with SARS-CoV-2 in pregnancy are reviewed and reported. Based on the literature available at the moment, it can be assumed that the clinical course of COVID-19 disease may be complicated by pregnancy which could be associated with a higher mortality rate. It may also be assumed at the moment that transmission from mother to child in utero is unlikely. Breastfeeding is possible once infection has been excluded or the disease declared cured.Im Dezember 2019 traten in Wuhan in China erstmals Fälle mit Pneumonien unbekannter Ursache auf; in der Folge konnte rasch ein neues Coronavirus als Ursache der inzwischen als Coronavirus Disease 2019 (COVID-19) bezeichneten Erkrankung identifiziert werden. Seither sind Infektionen in vielen Ländern weltweit bestätigt worden, und die Fallzahl steigt stetig. Diese Übersichtsarbeit soll einen Überblick über das neue Severe Acute Respiratory Syndrome (SARS) Coronavirus 2 (SARS-CoV-2) geben und insbesondere mögliche Risiken und Komplikationen für schwangere Patientinnen ableiten. Hierfür wurde die verfügbare Literatur zu Infektionsfällen in der Schwangerschaft während der SARS-Epidemie 2002/2003, der seit 2012 laufenden MERS-(Middle-East-respiratory-syndrome-)Epidemie, sowie aktuelle Publikationen zu Infektionsfällen mit SARS-CoV-2 während der Schwangerschaft gesichtet und beschrieben. Zum aktuellen Zeitpunkt ist aufgrund dieser verfügbaren Literatur davon auszugehen, dass der Verlauf einer COVID-19-Erkrankung durch eine Schwangerschaft verkompliziert werden kann und diese mit einer höheren Mortalität assoziiert sei könnte. Es ist zudem aktuell davon auszugehen, dass eine Transmission von der Mutter auf das Kind in utero unwahrscheinlich ist. Stillen ist nach Ausschluss einer Infektion oder abgeheilter Erkrankung möglich.
Keywords: COVID-19; coronavirus; SARS-CoV-2; 2019-nCoV; pregnancy